Growth and nodulation in soybean cultivated on two substrata and treated with five rates of metolachlor - Amarante,Cassandro Vidal Talamini do (1995)
The effect of metolachlior [2-chloro-N-(2-ethyl-6-methylphenyl)-N-(2-methoxy-l-methylethyl) acetamide] at rates of 0.0, 1.5, 3.0, 4.5, and 6.0kg a.i./ha on the growth and nodulation of soybean cv. BR-4 cultivated on two substrata (soil and soil + sand) and inoculated with Bradyrhizobium japonicum (Kirchnea-1896) Jordan 1982, 137 (Denotes that this name has been validly published in the oficial publicadon, Intemational Joumal of Systematic Bacteriology), was studied under greenhouse conditions at Lages, SC, Brazil, in 1992-93. The experimental design was completely randomized with four replicates. The experimental unit was a container with two plants. Fifty-two days after the emergence (at R1 stage - beginning of flowering) the plants were harvested and evaluated for shoot, root, leaf and nodule dry matter, nodule number, and leaf area. The data were submitted to variance analysis and multiple polynomial regression. Increasing rates of metolachlor significantly reduced shoot, leaf and nodule dry matter and leaf area, the data following a linear polynomial regression, while root dry matter and nodule number were not affected. The interaction "rate x substratum" was not significant for all parameters studied. Except for root dry matter and nodule number, soybean growth was significantly reduced more on soil + sand than on soil, probably as a result of a nutritional effect. Visual phytotoxicity was not observed for all treatments.